Study of Electric charge induction with a three-dimensional model using the finite elements method - De Resende Camara, Alexandre (2019)
One of the first subjects studied in Electricity and Magnetism classes is how one can make an electrically neutral object be an electrically charged object. There are three ways to do it: charging by friction, charging by contact and charging by induction. Induction charging is a method used to charge an object without actually touching the object to any other charged object. In order to illustrate the explanation of how the process of charging an electrically neutral body by induction, a 3D model was built using the finite elements method to show the increasing of the surface charge density in a initially neutral sphere when the distance between this sphere and a negatively charged bar decreases.